Is sitting invisible? Exploring how people mentally represent sitting - Benjamin Gardner; Stuart Flint; Amanda L. Rebar; Stephen Dewitt; Sahana K. Quail; Helen Whall; Lee Smith (BMC, 2019)
Abstract Background Growing evidence suggests that prolonged uninterrupted sitting can be detrimental to health. Much sedentary behaviour research is reliant on self-reports of sitting time, and sitting-reduction interventions often focus on reducing motivation to sit. These approaches assume that people are consciously aware of their sitting time. Drawing on Action Identification Theory, this paper argues that people rarely identify the act of sitting as 'sitting' per se, and instead view it as an incidental component of more meaningful and purposeful typically-seated activities. Methods Studies 1 and 2 explored whether people mentioned sitting in written descriptions of actions. Studies 3-5 compared preferences for labelling a typically desk-based activity as 'sitting' versus alternative action identities. Studies 6 and 7 used card-sort tasks to indirectly assess the prioritisation of 'sitting' relative to other action descriptions when identifying similar actions. Results Participants rarely spontaneously mentioned sitting when describing actions (Studies 1-2), and when assigning action labels to a seated activity, tended to offer descriptions based on higher-order goals and consequences of action, rather than sitting or other procedural elements (Studies 3-5). Participants primarily identified similarities in actions based not on sitting, but on activities performed while seated (e.g. reading; Studies 6-7). Conclusion 'Sitting' is a less accessible cognitive representation of seated activities than are representations based on the purpose and implications of seated action. Findings suggest that self-report measures should focus on time spent in seated activities, rather than attempting to measure sitting time via direct recall. From an intervention perspective, findings speak to the importance of targeting behaviours that entail sitting, and of raising awareness of sitting as a potential precursor to attempting to reduce sitting time.